2022
DOI: 10.3389/fimmu.2022.818625
|View full text |Cite
|
Sign up to set email alerts
|

Role of ROS-Induced NLRP3 Inflammasome Activation in the Formation of Calcium Oxalate Nephrolithiasis

Abstract: Calcium oxalate nephrolithiasis is a common and highly recurrent disease in urology; however, its precise pathogenesis is still unknown. Recent research has shown that renal inflammatory injury as a result of the cell-crystal reaction plays a crucial role in the development of calcium oxalate kidney stones. An increasing amount of research have confirmed that inflammation mediated by the cell-crystal reaction can lead to inflammatory injury of renal cells, promote the intracellular expression of NADPH oxidase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 98 publications
(100 reference statements)
0
27
0
Order By: Relevance
“…ROS exacerbate inflammation, which in turn increases ROS production [ 64 ]. Recent studies demonstrated that HMGB1 was stimulated by inflammatory bodies of NLRB, and HMGB1 could in turn facilitate the formation of inflammatory bodies of NLRP3, forming positive feedback of inflammation, thus sustaining or even intensifying the inflammatory cascade reaction and making acute inflammatory damage [ 65 , 66 ]. This was also manifested in our correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…ROS exacerbate inflammation, which in turn increases ROS production [ 64 ]. Recent studies demonstrated that HMGB1 was stimulated by inflammatory bodies of NLRB, and HMGB1 could in turn facilitate the formation of inflammatory bodies of NLRP3, forming positive feedback of inflammation, thus sustaining or even intensifying the inflammatory cascade reaction and making acute inflammatory damage [ 65 , 66 ]. This was also manifested in our correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of regulating encrustation response to macrophage is shown in Figure 9. M 1 and its corresponding pro-inflammatory cytokines, TNF-α and IL-6, and oxidative stress molecules, property to promote the development of CaOx stones, were downregulated via diminishing the nuclear factor kB (NF-kB) signal pathway after contacting with PU-Cu stents (Song et al, 2016;Liu et al, 2022a). Lysosome rupture, ROS generation, and NLRP3 inflammasome activation were blocked in the process of macrophage engulfing (Jin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lumen blocking, stones can also activate the inflammatory response of the human body and ultimately lead to tissue injury under the control of related inflammatory meditators (Li et al, 2020;Liu et al, 2022a). Macrophages play an important role in the early inflammatory response, and diverse cytokines such as interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) are secreted (Liu et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…ROS also indirectly maintain the activity of this cascade by inactivating JNK‐inhibiting phosphatase 161 . Moreover, ROS can trigger NLRP3 activation to regulate macrophage pyroptosis 162 . In addition, ROS enhance the phosphorylation of IκB to activate NF‐κB 163 and participate in the activation of STAT1 and IRF5 164 .…”
Section: Signaling Pathways In Macrophagesmentioning
confidence: 99%